An insight of disinfection by-product (DBP) formation by alternative disinfectants for swimming pool disinfection under tropical conditions. (15th September 2016) - Yang, Linyan; Schmalz, Christina; Zhou, Jin; Zwiener, Christian; Chang, Victor W.-C.; Ge, Liya; Wan, Man Pun
Abstract: Sodium hypochlorite (NaClO) is the most commonly used disinfectant in pool treatment system. Outdoor pools usually suffer from the strong sunlight irradiation which degrades the free chlorine rapidly. In addition, more pools start to adopt the recirculation of swimming pool water, which intensifies the disinfection by-product (DBP) accumulation issue. Given these potential drawbacks of using NaClO in the tropical environment, two alternative organic-based disinfectants, trichloroisocyanuric acid (TCCA, C3 Cl3 N3 O3 ) and bromochlorodimethylhydantoin (BCDMH, C5 H6 BrClN2 O2 ), were investigated and compared to NaClO in terms of their self-degradation and the formation of DBPs, including trihalomethanes (THMs) and haloacetic acids (HAAs), under simulated tropical climate conditions. The result reveals that halogen stabilizer, TCCA, had the advantages of slower free chlorine degradation and lower DBP concentration compared to NaClO, which makes it a good alternative disinfectant. BCDMH was not recommended mainly due to the highly reactive disinfecting ingredient, hypobromous acid (HBrO), which fails to sustain the continuous disinfection requirement. Total disinfectant dosage was the main factor that affects residual chlorine/bromine and THM/HAA formation regardless of different disinfectant dosing methods, e.g. shock dosing (one-time spiking) in the beginning, and continuous dosing during the whole experimental period. Two-stage second-order-kinetic-based models demonstrate a good correlation between the measured and predicted data for chlorine decay ( R 2 ≥ 0.95), THM ( R 2 ≥ 0.99) and HAA ( R 2 ≥ 0.83) formation. Higher temperature was found to enhance the DBP formation due to the temperature dependence of reaction rates. Thus, temperature control of pools, especially for those preferring higher temperatures (e.g. hydrotherapy and spa), should take both bather comfort and DBP formation potential into consideration. It is also observed that chlorine competition existed between different precursors from natural organic matters (NOM) in filling water and body fluid analogue (BFA). Among the composition of BFA, uric acid, citric acid and hippuric acid were found to be the main precursors for HAA formation. Graphical abstract: Highlights: Trichloroisocyanuric acid shows higher residual chlorine and lower DBPs than NaClO. Residual Cl/Br and DBP formation depend mainly on dosage instead of dosing methods. Two-stage models provide good fitting for both chlorine decay and DBP formation. Chlorine competition exists between precursors of different DBP species. Uric acid, citric acid and hippuric acid are main precursors of haloacetic acids.